Urban Planning Education Beginnings, Global Movement and Future Prospects (The Urban Book Series,, 2018)
This book examines planning education systems and approaches globally, through a comparative and longitudinal perspective. It explores the emergence of planning education in the 20th century, with its rich variation and yet a remarkable degree of cross-fertilization. Each of the sections of the book is framed by an overview essay which has been prepared by the editors to provide the reader with a critical exposure to relevant scholarship drawing on the detailed case studies and exploratory essays on key issues in planning education. The first part of this volume focuses on the emergence of planning education programs in the twentieth century as a way to understand the current planning education environment. Then we explore how education in urban, regional and spatial planning has developed in different ways in different countries and continents. The final part of this volume aims to envision how planning can adapt and develop to remain relevant to the development of human environments in the 21st century. Urban planning education has become a pervasive practice throughout the world as urbanization and development pressures have increased over the past half century, and as demand increased for professional trained experts to guide those processes. The approaches vary widely, based in part upon the discipline from which the planning program developed as well as the context-specific challenges within the country or region where the program resides.